The Timely Habituation of Thematic Learning in Elementary School - Ridha Hasniar; Sutama Sutama (AL-ISHLAH: Jurnal Pendidikan, 2023)
Education is not only a teaching and learning process also necessitates thematic learning habits in elementary schools. It is still not optimal to familiarize elementary school students with time. There still students who are late for class, do not complete tasks on time, and do not engage in thematic learning processes. The aim of this research is to find out the timeliness of learning, including starting learning on time and doing assignments on time. This research is a qualitative descriptive study. The research was conducted at SD Negeri 5 Purwosuman Sragen with the principal, class teacher, and students. The data collection method was the non-test method, namely observation and interviews. Data analysis was carried out through qualitative descriptive analysis using data reduction, data presentation, and drawing conclusions or testing. The results of this study show that students are not on time in starting to study and do assignments, so they still need habituation so that they can be on time. A timely habituation in thematic learning must be followed by students' awareness of their role in the learning process.